2018
DOI: 10.5114/wo.2018.78947
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the relation between religiosity, mental health, and psychological resilience in breast cancer patients

Abstract: Aim of the studyThe aim of this study was to examine the relationship between religiosity, mental health, and psychological resilience in breast cancer patients.Material and methodsA cross-sectional study was conducted in an oncology department of a hospital in northern Greece during February and March 2017. The sample consisted of 152 breast cancer patients. Data were collected with the following instruments: Patient Health Questionnaire two-item scale, Generalised Anxiety Disorder two-item scale, Connor-Davi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
27
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 27 publications
(25 reference statements)
7
27
1
6
Order By: Relevance
“…Our findings align with previous research where religiosity was positively associated with resilience (Choi & Hastings, 2019;Fradelos et al, 2018). Religiousness is often regarded as a source of strength for buffering the effects of adversity (Pargament & Cummings, 2010 The low values from this table (which become zero if rounded to one digit) have been presented as percentages.…”
Section: Resilience and Personal Factorssupporting
confidence: 89%
“…Our findings align with previous research where religiosity was positively associated with resilience (Choi & Hastings, 2019;Fradelos et al, 2018). Religiousness is often regarded as a source of strength for buffering the effects of adversity (Pargament & Cummings, 2010 The low values from this table (which become zero if rounded to one digit) have been presented as percentages.…”
Section: Resilience and Personal Factorssupporting
confidence: 89%
“…The qualitative study by Ahaddour and Broeckaert (2018) reported that religious approaches of Muslim women who were diagnosed with cancer such as thinking of the disease as a condition from God affected patients positively on coping with the problems caused by the disease (Ahaddour and Broeckaert, 2018). Previous studies in the literature conducted with women with breast cancer reported that religious practices (prayer and meditation) contributed to the mental adjustment of women with cancer to the disease (Ng et al, 2017; Saso et al, 2017; Fradelos et al, 2018; Park et al, 2018; Karabulutlu et al, 2019). Also, studies conducted in Turkey have indicated that religious practices were common among gynecologic cancer patients (Nazik et al, 2012; Duman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies have focused primarily on negative psychological and behavioral responses such as anxiety and depression [8,9], fear of progression/relapse [10,11], decreased self-e cacy [12], poor perception of social support [13,14], and negative coping strategies [15]. Few studies have examined the direct and indirect effects of resilience on the physical, psychological, and social functioning of women with breast cancer [7,16,17], and studies of women who have been newly diagnosed are even more limited.…”
Section: Introductionmentioning
confidence: 99%